Desempeño de los sistemas acuícolas de recirculación en el cultivo intensivo del Pacú Piaractus mesopotamicus (Characiformes: Characidae). - Domínguez Castanedo, Omar (2012)
An alternative to intensify fish production, reducing the environmental impact and production costs are recirculating aquaculture systems (RAS). The performance of a RAS was evaluated, as fish growth and water quality conditions, in a culture of Piaractus mesopotamicus reared for ornamental purposes. Two commercial food brands with different protein contents (18%-TI and 28%-T2), were given to juvenile fishes during an eight weeks period. Growth was measured bi-weekly: standard length (Lp), peak height (A), weight and multiple condition factor (KM). The evaluation of water parameters included: dissolved oxygen, NH3-NH4, pH, NO2, NO3, KH carbonate hardness and PO4. NH3-N rate production was analyzed following Timmons-Ebeling model. Results demonstrated significant differences in weight only, and T2 showed a 7.5% higher value than T1; nevertheless, treatment T1 had a higher KM. In general, water quality values were suitable for growth: OD=T1: 4.23±1.23; T2: 4.13±0.86; NH3=T1: 0.02±0.02; T2: 0.06±0.10; however, pH was an exception (T1: 6.95±0.98; T2: 7.11±1.03), displaying lethal rates (<5) by the fifth week. Systems NH3 removal had a 99.4% to 100% efficiency. Final fish biomass was 22.03kg for T1 and 27.49kg for T2. We concluded that the systems were able to maintain suggested density up to the experimental fifth week. Water quality parameters remained in suitable levels, with the pH exception. Cultured fishes reached their commercial size (10cm) in eight weeks.